Análise e classificação de diferentes marcas de arroz beneficiado polido branco dos municípios de Alegrete/RS e Pelotas/RS utilizando a legislação vigente - (:unkn) unknown (Universidade Federal do Pampa, 2018)
One of the biggest challenges in the commercialization of grains, in the act of buying or selling, is the guarantee of the correct conservation of the product, although guaranteeing food and nutritional security to the final consumer public. In Brazil there are laws in force that address the classification of products of plant origin, addressing minimum indexes so that these products can complete the table of the consumed. Therefore, the analysis and classification of grains are extremely important because it allows standardization of grains in commerce. Rice is considered to be the most economically important product in many developing countries, constituting itself as a staple food because it has great adaptability to different soil and climate conditions. The legislation governing the classification of plants is Law No. 9,972 of May 25, 2000, which establishes the classification of plant products, by-products and wastes of economic value, and other measures. The rice has a normative Instruction that the Ministry of Agriculture Livestock and Supply provides and that marks the classification for the white polished rice benefited. With this, the general objective of this work is to classify according to Normative Instruction Nº 06/2009 different brands of white polished beneficiated rice from the municipalities of Alegrete / RS and Pelotas / RS. As specific objectives will be made a comparative analysis of how the same product, but different regions are presented in the final consumer market, if they respect the limits allowed by the standard, thus ensuring food and nutritional security. For this study 4 (four) different brands from the municipalities of Alegrete / RS and Pelotas / RS were chosen with 3 (three) replicates for each brand, it is concluded that in this study there was no significant difference with the Tukey test with probability of 5% between the white polished beneficiated rice brands of the western border region of RS and the southern region of RS. This means that all the evaluated products are within the conformities required by current legislation, which guarantees food and nutritional security for all evaluated products.
Analysis and classification of different rice brands beneficiated white polish of the municipalities of Alegrete / RS and Pelotas / RS using the current legislation
Keywords: Engenharia agrícola; Grãos; Análise; Classificação; Defeitos; Qualidade; Agricultural engineering; Grains; Analyze; Ranking; Defects; Quality; CNPQ::CIENCIAS AGRARIAS